A Population‐Based Cross‐Sectional Study Comparing Breast Cancer Stage at Diagnosis between Immigrant and Canadian‐Born Women in Ontario - Iqbal, Javaid; Ginsburg, Ophira; Fischer, Hadas D.; Austin, Peter C.; Creatore, Maria I.; Narod, Steven A.; Rochon, Paula A. (The breast journal, 2017)
There is limited information on stage at breast cancer diagnosis in Canadian immigrant women. We compared stage at diagnosis between immigrant women and Canadian‐born women, and determined whether ethnicity was an independent factor associated with stage. 41,213 women with invasive breast cancer from 2007 to 2012 were identified from the Ontario Cancer Registry. Women were classified as either immigrants or Canadian‐born by linkage with the Immigration, Refugees, and Citizenship Canada's Permanent Resident database. Women's ethnicity was classified as Chinese, South Asian, or remaining women in Ontario. Logistic regression was performed to calculate the odds ratio (OR) of being diagnosed at stage I breast cancer (versus stage II–IV). 4,353 (10.6%) women were immigrants and 36,860 (89.4%) were Canadian‐born women. The mean age at breast cancer diagnosis was 53.5 years for immigrants versus 62.3 years for Canadian‐born women (p < 0.0001). Immigrant women were less likely than Canadian‐born women to be diagnosed with stage I breast cancers (adjusted OR = 0.85; 95% CI: 0.79–0.91; p < 0.0001). The adjusted OR of being stage I was 1.28 (95% CI: 1.14–1.43; p < 0.0001) for women of Chinese ethnicity and was 0.82 (95% CI: 0.70–0.96; p = 0.01) for women of South Asian ethnicity, compared to the remaining women in Ontario. Canadian immigrant women were less likely than Canadian‐born women to be diagnosed with early‐stage breast cancers. Ethnicity was a greater contributor to the stage disparity than was immigrant status. South Asian women, regardless of immigration status, might benefit from increased breast cancer awareness programs.